2011
DOI: 10.1002/cssc.201000254
|View full text |Cite
|
Sign up to set email alerts
|

Ionic Liquid‐Based Membranes as Electrolytes for Advanced Lithium Polymer Batteries

Abstract: Gel-type polymer electrolytes are formed by immobilizing a solution of lithium N,N-bis(trifluoromethanesulfonyl)imide (LiTFSI) in N-n-butyl-N-ethylpyrrolidinium N,N-bis(trifluoromethanesulfonyl)imide (Py₂₄TFSI) ionic liquid (IL) with added mixtures of organic solvents, such as ethylene, propylene and dimethyl carbonates (EC, PC, and DMC, respectively), into a poly(vinylidenefluoride-co-hexafluoropropylene) (PVdF-HFP) matrix, and their properties investigated. The addition of the organic solvent mixtures result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(32 citation statements)
references
References 25 publications
0
32
0
Order By: Relevance
“…[270] Similarly,Y ee tal., [271] Navarra et al, [272] and Hofmann et al [273] reported very promising resultsi nt erms of safety and electrochemical performance for PVdF-HFP-based quaternary electrolyte systems; this also revealed good compatibility with graphite anodes and Li(Ni 1/3 Mn 1/3 Co 1/3 )O 2 cathodes. Nevertheless, intrinsic safety issues related to the utilization of volatile and flammable organic solvents might be substantially reduced, but not completely overcome.…”
Section: Alkyl Carbonate/il/solid Polymer Blends (Ole-il-spes)mentioning
confidence: 88%
“…[270] Similarly,Y ee tal., [271] Navarra et al, [272] and Hofmann et al [273] reported very promising resultsi nt erms of safety and electrochemical performance for PVdF-HFP-based quaternary electrolyte systems; this also revealed good compatibility with graphite anodes and Li(Ni 1/3 Mn 1/3 Co 1/3 )O 2 cathodes. Nevertheless, intrinsic safety issues related to the utilization of volatile and flammable organic solvents might be substantially reduced, but not completely overcome.…”
Section: Alkyl Carbonate/il/solid Polymer Blends (Ole-il-spes)mentioning
confidence: 88%
“…[18] Ionic liquids( ILs) have been investigatedf or the preparation of electrolytes for Mg batteries because, in addition to having high thermala nd electrochemical stability,t hey exhibit negligible vapour pressure and are non-flammable. [19][20][21] Furthermore, ILs enable the use of oxide-based cathodic materials, which show as uperior specificc apacity and operating voltage with respectt oc onventionalC hevrel-phase materials. [22] However,i t has been reportedt hat Mg electrodes are generally reactive toward imidazolium-based ILs.…”
Section: Introductionmentioning
confidence: 99%
“…ILs are generally known to possess undetectable vapour pressure, wide liquid temperature range, high solubility for many organic and inorganic compounds, and low toxicity [1][2][3]. Hence, ILs are applied in many chemical and industrial processes such as CO 2 capture [4][5][6], battery development [7,8], electrochemical applications [9] and biocatalysts [10,11], organic synthesis [12], material synthesis [13], extraction [5], and biomedical applications [5].…”
Section: Introductionmentioning
confidence: 99%